Sometimes I kaploom - Vail, Rachel (Orchard Books, an imprint of Scholastic Inc., 2023)
"Katie Honors is a really brave kid. She can go to bed with just one small night light. She can hold her tears in when it's time to say goodbye to her mom at school. But sometimes Katie isn't ready to say goodbye and doesn't feel brave at all. When this happens, she Kaplooms! She refuses to let go of her mom, and everything is flurried as she begins to cry. Her emotions feel frightening. It's not the Katie Honors she wants to be. But her mother assures Katie that she can be both brave and sad, brave and crying, brave and scared. Sometimes I Kaploom masterfully explores how hard it can be for children when they're nervous or scared and have to transition to new places and faces when they just don't feel quite ready. In another poignant, honest, and insightful story, readers learn along with Katie that bravery and fear are not mutually exclusive"--